A review on the bioavailability, bio-efficacies and novel delivery systems for piperine. Issue 19 (16th September 2021) - Zhang, Weiyun; Zheng, Qianwang; Song, Mingyue; Xiao, Jie; Cao, Yong; Huang, Qingrong; Ho, Chi-Tang; Lu, Muwen
Abstract : The bioavailability, bio-efficacies and novel delivery systems for piperine were reviewed. Abstract : As the major naturally occurring alkaloid in pepper with a pungent taste, piperine is known for its beneficial biological functions and therapeutic effects. In this work, the bioavailability and biological activities of piperine were presented and discussed. Novel delivery systems for enhancing the bioavailability of piperine were also reviewed. This study could provide a better understanding of the physiological and biochemical aspects of piperine to be further developed in the food and nutraceutical industries.